The comparison of the wrestlers` status of some physical, physiological and growth hormone status after resting, competition and sauna sessions - Kiyici, F.; Ucan, I. (Procedia - Social and Behavioral Sciences, 2014)
The aim of this study is to compare some of the physical, physiological, and growth hormone status during the resting, training and after the sauna sessions (80-100 °C and10-15% humidity) for wrestlers. Blood samples, for Growth Hormone (GH) were taken and stored during resting time, before breakfast in the morning, after training and the completion of sauna sessions. According to the results of the study; in body temperature and during resting and after training and sauna sessions (p<0.01), in the number of heart beats (NOV), both between resting status and training, sauna sessions and between training and sauna sessions (p<0.01), in reaction time (with right and left hand) both between resting status and training, and between training and sauna sessions (p<0.01), in GH both between resting time and sauna sessions, and between training and sauna sessions, results were stated statistically significant (p<0.01).